A tribological investigation of water-based nanolubricants prepared by mechanically synthesised hBN/TiO2 nanocomposites - Afshana Morshed; Fei Lin; Hui Wu; Zhao Xing; Sihai Jiao; Zhengyi Jiang (Nano Express)
Environmentally friendly synthesis techniques have gained increasing attention as viable methodologies for preparing nanocomposite. In particular, ball milling has emerged as a green and cost-effective method that ensures the control of size, shape and morphology to generate nanocomposites without compromising sample quality or purity. In this work, a wet milling technique was employed to synthesise hBN/TiO _2 nanocomposites, which were characterised via XRD, XPS, and TEM. The results demonstrated that milling for 6 h with a 1:5 powder-to-ball ratio effectively deagglomerated and evenly distributed TiO _2 nanoparticles within the hBN nanosheets by promoting the formation of B-O interactions between the boron of hBN and oxygen of TiO _2 . Water-based lubricants prepared using the as-synthesised hBN/TiO _2 nanocomposites showed stable dispersion for up to 5 days, regardless of the milling conditions. Tribological tests via a ball-on-disk tribometer revealed that water-based lubricants with optimally milled nanocomposite exhibited outstanding tribological performance by reducing the average COF and wear by 78.4 and 91.3%, respectively, compared with dry conditions. However, extending the milling duration negatively affected the overall performance of the nanocomposites. The lubrication mechanism is attributed to the synergistic effect of both hBNNSs and TiO _2 NPs; layered hBN contributed to protective film formation, whereas TiO _2 NPs assisted in rolling and mending effects during the sliding process.